Answer:
Let z = f(x, y) where f(x, y) =0 then the implicit function is
![\frac{dy}{dx} =](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7Bdx%7D%20%3D)
![\frac{-δ f/ δ x }{δ f/δ y }](https://tex.z-dn.net/?f=%5Cfrac%7B-%CE%B4%20f%2F%20%CE%B4%20x%20%7D%7B%CE%B4%20f%2F%CE%B4%20y%20%7D)
Example:- ![\frac{dy}{dx} = \frac{-(y+2x)}{(x+2y)}](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7Bdx%7D%20%20%3D%20%5Cfrac%7B-%28y%2B2x%29%7D%7B%28x%2B2y%29%7D)
Step-by-step explanation:
<u>Partial differentiation</u>:-
- Let Z = f(x ,y) be a function of two variables x and y. Then
Exists , is said to be partial derivative or Partial differentiational co-efficient of Z or f(x, y)with respective to x.
It is denoted by δ z / δ x or δ f / δ x
- Let Z = f(x ,y) be a function of two variables x and y. Then
Exists , is said to be partial derivative or Partial differentiational co-efficient of Z or f(x, y)with respective to y
It is denoted by δ z / δ y or δ f / δ y
<u>Implicit function</u>:-
Let z = f(x, y) where f(x, y) =0 then the implicit function is
![\frac{dy}{dx} =](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7Bdx%7D%20%3D)
![\frac{-δ f/ δ x }{δ f/δ y }](https://tex.z-dn.net/?f=%5Cfrac%7B-%CE%B4%20f%2F%20%CE%B4%20x%20%7D%7B%CE%B4%20f%2F%CE%B4%20y%20%7D)
The total differential co-efficient
d z = δ z/δ x +
δ z/δ y
<u>Implicit differentiation process</u>
- differentiate both sides of the equation with respective to 'x'
- move all d y/dx terms to the left side, and all other terms to the right side
- factor out d y / dx from the left side
- Solve for d y/dx , by dividing
Example : ![x^2 + x y +y^2 =1](https://tex.z-dn.net/?f=x%5E2%20%2B%20x%20y%20%2By%5E2%20%3D1)
solution:-
differentiate both sides of the equation with respective to 'x'
![2x + x \frac{dy}{dx} + y (1) + 2y\frac{dy}{dx} = 0](https://tex.z-dn.net/?f=2x%20%2B%20x%20%5Cfrac%7Bdy%7D%7Bdx%7D%20%2B%20y%20%281%29%20%2B%202y%5Cfrac%7Bdy%7D%7Bdx%7D%20%3D%200)
move all d y/dx terms to the left side, and all other terms to the right side
![x \frac{dy}{dx} + 2y\frac{dy}{dx} = - (y+2x)](https://tex.z-dn.net/?f=x%20%5Cfrac%7Bdy%7D%7Bdx%7D%20%20%2B%202y%5Cfrac%7Bdy%7D%7Bdx%7D%20%3D%20%20-%20%28y%2B2x%29)
Taking common d y/dx
![\frac{dy}{dx} (x+2y) = -(y+2x)](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7Bdx%7D%20%28x%2B2y%29%20%3D%20-%28y%2B2x%29)
![\frac{dy}{dx} = \frac{-(y+2x)}{(x+2y)}](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7Bdx%7D%20%20%3D%20%5Cfrac%7B-%28y%2B2x%29%7D%7B%28x%2B2y%29%7D)